Book Launch: Decolonization and Afro-Feminism - Firoze Manji (2020)
Sylvia Tamale, author of Decolonization and Afro-Feminism, will be discussing her new book with Charmaine Pereira, writer and feminist scholar in Abuja, Nigeria. Host: Firoze Manji, Publisher, Daraja Press September 24, 2002
Keywords: afrique; afro-féminisme; approches et analyses; cours; fem3300; féminisme africain; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions